The relationship between knowledge of cardiovascular disease risk factors and health anxiety among caregivers of patients undergoing open-heart surgery - Dolapoğlu, Nazan; Dolapoglu, Ahmet; Altunöz, Sinan; Barbarus, Emin (The European Research Journal, 2025)
Objectives: Cardiovascular diseases, characterized by their chronic nature, frequently lead to considerable physical strain and psychological distress in affected individuals. In managing these challenges, the involvement of caregivers plays a pivotal role. The effectiveness and consistency of the care they offer are substantially influenced by both their psychological health and their understanding of the disease’s risk profile. This study aims to examine the relationship between caregivers’ knowledge of cardiovascular risk factors and their levels of health anxiety while caring for patients recovering from open-heart surgery. Methods: Participants who were identified as caregivers for individuals undergoing open-heart surgery were assessed using three instruments: a demographic and descriptive questionnaire, the Cardiovascular Disease Risk Factors Knowledge Level Scale (CARRF-KL), and the Health Anxiety Inventory (HAI). Results: The study included 58 participants, with females comprising 56.9% of the sample. The average score obtained on the Cardiovascular Disease Risk Factors Knowledge Level Scale (CARRF-KL) was 19.16±4.99, whereas the mean score on the Health Anxiety Inventory (HAI) was 21.1±14.84. The analysis showed a statistically significant, positive but weak correlation between the total scores of the Health Anxiety Inventory (HAI) and the Cardiovascular Disease Risk Factors Knowledge Level Scale (CARRF-KL) (r= 0.282, P=0.032). Additionally, participants’ education levels were significantly related to their CARRF-KL scores (P